Critical pedagogy and beyond - Gounari, Panayota; Morelock, Jeremiah; Narita, Felipe Ziotti (Cadernos CIMEAC, 2022)
An interview with Panayota Gounari. The interview was organized and coordinated by Jeremiah Morelock and Felipe Ziotti Narita.